Scientific Journals of Universities of Chile, Colombia, and Venezuela: Actors and Roles - Jorge Enrique Delgado Troncoso (Arizona State University, 2014)
A qualitative study was carried to identify the roles of actors associated with the publication of scientific journals in Chilean, Colombian, and Venezuelan universities. Twenty-four semi-structured in-depth interviews were conducted with journal editors, university authorities, and other experts. The categories of analysis included university leaders (journal directors/coordinators), institutional actors (university presses and libraries), and journal editors. Changes emphasizing open access journals and salary incentives to increase productivity among university professors are creating new roles for those involved in the publication of journals. University journal directors and coordinators are being challenged to provide support and to seek inclusion in national and international indexes. Although university presses have not played an important role in this process, libraries have gained new responsibilities associated with data processing and the creation of repositories. Challenges exist for individual editors to obtain supporting personnel, as journal publication work grows and demands more.